The adaptive value associated with expressing and perceiving angry-male and happy-female faces - Tay, Peter Kay Chai (Frontiers in Psychology, 2015)
Facial expressions are valuable for conveying and understanding the inner thoughts and feelings of the expressor. However, the adaptive value associated with a specific expression on a male face is different from a female face. The present review uses a functional-evolutionary analysis to elucidate the evolutionary advantage in the expression and perception of angry-male and happy-female faces over angry-female and happy-male faces. For the expressors, it is more advantageous for men to show angry facial expression as it signals dominance, averts aggression and deters mate poaching; it is more advantageous for women to display happy facial expression as it signals their willingness for childcare, tending and befriending. For the perceivers, those sensitive to angry men avoid being physically harmed while those sensitive to happy women gain social support. Extant evidence suggests that facial structure and cognitive mechanisms evolved to express and perceive angry-male and happy-female faces more efficiently compared to angry-female and happy-male faces.